Resistance of Broiler Meat through Exposure to Extremely Low Frequency Magnetic Fields of 700 µT and 900 µT Intensities and Safety Risks to Health - Sudarti Sudarti; Lutfiana Ditta Sari; Elok Permatasari; Tania Ardiani (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to examine "Resistance of broiler chicken meat through exposure to ELF MF and safety risks to health". Research samples of 140 packs of fresh broiler chicken meat (@ 50 grams) were divided into seven groups (@ 20 packs), one group as control, 3 groups were exposed to ELF MF intensity of 700 µT each with an exposure duration of 30, 45 and 60 minutes, and 3 groups were exposed to ELF MF intensity of 900 µT with exposure durations of 30, 40, and 60 minutes, respectively. Indicators of chicken meat resistance include pH, density, texture, color, aroma, and the appearance of mucus in chicken meat samples that have been stored for 6, 12, 18, and 24 hours after exposure to ELF MF. Research results: the physical endurance of chicken meat stored for 12 hours after being exposed to ELF MF intensity of 700 µT and 900 µT was better than the control. Conclusion: exposure to ELF MF intensity of 900 µT for 45 minutes and 60 minutes is able to maintain the quality of chicken meat at room temperature for up to 12 hours of storage and is safe for health.